Necesidades de información de los médicos de atención primaria: análisis de preguntas y su resolución()() - González-González, A.I. (Aten Primaria, 2005)
OBJECTIVE: To assess what information primary care doctors from 5 health areas of Madrid need, through the description of the frequency and kind of clinical questions that arise, the pattern of search for the answers and how well they were answered. DESIGN: Descriptive, observational study. SETTING: Primary care consultations in health areas 1, 3, 8, 9, and 10, Madrid, Spain. PARTICIPANTS: Randomised sample, stratified by zone, and kind of doctor, of 125 doctors from each area (Madrid). Residents, locums, and university teachers were excluded. INTERVENTIONS: Doctors will be invited to be observed by video camera for about four hours of on-demand consultation. They will be asked between patients to specify the questions that arise and the sources of information used in the consultation. Unresolved questions will be followed up by means of phone contact 2 weeks later, to see whether they had found answers and what methods they used to find them. MAIN MEASUREMENTS: Main variables: number of recognised clinical questions formulated and their answers; number of clinical questions not recognised (as observed by video); each question's theme and kind of information; time used to look for answers; information resources used.Other variables: characteristics of the PC professionals taking part, consultations, health centres, and caseloads. DISCUSSION: Restrictions: Hawthorne effect or bias in the person observed and participants’ stage fright. Applicability: the results of the research will be used to plan the resources needed for doctors to enjoy and put into practice the best scientific knowledge.